2023
DOI: 10.1097/hjh.0000000000003394
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of liver fibrosis scores in cardiovascular diseases among hypertensive population

Abstract: Purpose: To explore the predictive value of liver fibrosis scores [fibrosis-4, AST/platelet ratio index, BAAT score (BMI Age ALT TG), and BARD score (BMI AST/ALT Ratio Diabetes)] for the risk of cardiovascular disease (CVD) in a hypertensive population. Methods: A total of 4164 hypertensive participants without history of CVD were enrolled in the follow-up. Four liver fibrosis scores (LFSs) were used, including the fibrosis-4 (FIB-4), APRI, BAAT score, and BARD score. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“… 21 Xiong et al suggested that the liver fibrosis score (FIB-4 and APRI) could predict the risk of cardiovascular disease (CVD) in a hypertensive population. 22 …”
Section: Discussionmentioning
confidence: 99%
“… 21 Xiong et al suggested that the liver fibrosis score (FIB-4 and APRI) could predict the risk of cardiovascular disease (CVD) in a hypertensive population. 22 …”
Section: Discussionmentioning
confidence: 99%
“…FIB-4I can potentially predict the future cardiovascular events in patients with HTN [30]. When using a low FIB-4I value as the reference, the instances of cardiovascular events was reported to be significantly higher in medium and high categories (HRs = 1.88 and 2.98, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…HTN is one of the most important coronary risk factors [ 21 , 25 ] and is closely associated with the development of MACEs. Xiong et al reported that the liver fibrosis score was associated with cardiovascular disease in hypertensive populations in northeastern China [ 26 ]. The prevention of MACEs and further strengthening risk stratification for hypertensives are very important.…”
Section: Discussionmentioning
confidence: 99%